The ASEAN Free Trade Agreement : Impact on Trade Flows and External Trade Barriers - Calvo-Pardo, Hector; Freund, Caroline; Ornelas, Emanuel (2012)
Using detailed data on trade and tariffs from 1992-2007, the authors examine how the ASEAN Free Trade Agreement has affected trade with nonmembers and external tariffs facing nonmembers. First, the paper examines the effect of preferential and external tariff reduction on import growth from ASEAN insiders and outsiders across HS 6-digit industries. The analysis finds no evidence that preferential liberalization has led to lower import growth from nonmembers. Second, it examines the relationship between preferential tariff reduction and MFN tariff reduction. The analysis finds that preferential liberalization tends to precede external tariff liberalization. To examine whether this tariff complementarity is a result of simultaneous decision making, the authors use the scheduled future preferential tariff reductions (agreed to in 1992) as instruments for actual preferential tariff changes after the Asia crisis. The results remain unchanged, suggesting that there is a causal relationship between preferential and MFN tariff reduction. The findings also indicate that external liberalization was relatively sharper in the products where preferences are likely to be most damaging, proving further support for a causal effect. Overall, the results imply that the ASEAN agreement has been a force for broader liberalization.